Carrot or stick? The impact of paternalistic leadership on the behavioral integration of top management teams in megaprojects. Issue 5 (7th May 2020) - Wan, Jingyuan; Le, Yun; Wang, Ge; Xia, Nini; Liu, Xiaoxue
Abstract : Purpose: Following the call to explore what leadership theory could be applicable in temporary organizations, the purpose of this study was to develop an integrative model linking the effects of paternalistic leadership styles (i.e. authoritarian, benevolent and moral) on the behavioral integration (BI) of top management teams (TMTs) in megaproject settings. Design/methodology/approach: The performance of the research model was tested based on empirical data collected from a sample of 43 megaproject TMTs. Findings: The results show that the moral leadership style can significantly stimulate the BI of TMTs, whereas authoritarian leadership has a negative impact and benevolent leadership has no significant impact. Furthermore, trust in leader plays a partial mediating role between paternalistic leadership and BI, and the power distance value of TMT positively moderates the links between authoritarian and moral leadership styles and BI. Research limitations/implications: The TMT sample was drawn from China's megaprojects, most of which have global influence (e.g. Hong Kong–Zhuhai–Macao Bridge and Shanghai Expo), but the sampling approach limits the generalizability of the research findings to other contexts. Originality/value: This study introduces the concept of BI into the realm of megaproject management and provides a novel perspective (i.e. paternalistic leadership) for exploring its antecedents. The findings, therefore, contribute to the literature by broadening the megaproject management research with a microfoundation perspective and by extending the extant paternalistic leadership in the context of temporary organizational settings.